Alkali-activated 3D printable concrete containing iron tailings and preparation method of alkali-activated 3D printable concrete

By optimizing the assembly distribution ratio and ball mill activation treatment of iron tailings powder, alkali-excited concrete slurry with good flow was prepared, which solved the problems of high cost of 3D-printed concrete materials and unreachable application potential of iron tailings, and achieved the improvement of the constructability and mechanical properties of efficient 3D-printed building structures.

CN119774973APending Publication Date: 2025-04-08HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510003136.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing 3D printed concrete materials are costly, and the application of iron tailings in 3D printing technology has not yet reached the potential for resource utilization, making it difficult to meet the constructionability and printing accuracy requirements of 3D printed concrete.

Method used

The alkali-excited 3D printed concrete with iron tailings is used to treat iron tailings powder. By optimizing the assembly distribution ratio and ball mill activation, an alkali-excited concrete slurry with good flow is prepared, and the particles are refined by mechanical grinding, increasing the specific surface area, activating the volcanic ash activity, and promoting the dissolution and hydration reaction of the silicon-aluminum glass phase.

Benefits of technology

It significantly improves the constructability and printing accuracy during the 3D printing process, enhances the uniform dispersion and mechanical properties of the gelled materials, reduces production costs, complies with the 32.5 grade standard of General Silicate Cement, and significantly improves the early compressive strength under standard maintenance conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774973A_ABST
    Figure CN119774973A_ABST
Patent Text Reader

Abstract

The invention relates to alkali-activated 3D printable concrete containing iron tailings and a preparation method of the alkali-activated 3D printable concrete, and belongs to the technical field of 3D printing building materials. In order to solve the problem that existing 3D printable concrete is high in cost, the alkali-activated 3D printable concrete containing iron tailings is provided and comprises iron tailing powder, fly ash, mineral powder, steel slag, fine aggregate and an alkali activator, and the fine aggregate contains 0-20% of iron tailing sand. By utilizing the volcanic ash activity of the iron tailing powder, the concrete strength is improved, so that the concrete can meet the requirements of 3D printing. The concrete slurry with good fluidity is obtained by optimizing the component proportion, the modeling and printing precision of the concrete slurry in the 3D printing process is remarkably improved, and the overall performance of a 3D printing building structure is optimized. The method is low in energy consumption, low in carbon emission and high in technical operation feasibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing building materials, and in particular relates to an alkali-activated 3D printable concrete containing iron tailings and a preparation method thereof. Background Art

[0002] In the field of civil engineering, 3D printing technology has become a hot topic in the construction industry due to its advantages such as short construction period, low manpower input, high construction accuracy and strong design flexibility. However, it is worth noting that the total cost of 3D printed concrete (3DPC) materials is still higher than that of traditional concrete structures. The main reason for this difference is the high consumption of cement in traditional concrete production. Therefore, seeking low-cost and sustainable building materials to replace traditional cement has become an important issue that needs to be solved urgently.

[0003] Fly ash, mineral powder and steel slag have been widely recognized as cement substitutes in ordinary concrete. These substitutes can improve the working performance of concrete, increase the strength and durability of concrete, and reduce production costs. However, the application of these materials in 3D printed concrete is limited. 3D printed concrete needs to have a controllable hydration reaction rate and setting time to ensure the stability and strength development of concrete during the printing process. However, the hydration reaction rate of fly ash, mineral powder and steel slag may be different from that of ordinary cement, which may cause the 3D printed concrete to set too fast or too slow during the printing process, affecting the printing quality and efficiency. When fly ash, mineral powder or steel slag replaces cement at a high ratio, it may cause the concrete to be too viscous or difficult to extrude.

[0004] Iron tailings are solid waste discharged after the iron ore is crushed, ground, and sorted, and are the main component of industrial solid waste. Iron tailings not only waste a lot of land and natural resources in the process of degradation, landfill, storage, and transformation, but also cause soil and water pollution, posing a potential threat to the ecological environment and human health. The resource utilization of iron tailings has become an inevitable trend. In recent years, with the advancement of technology, the application of iron tailings in the preparation of ordinary alkali-activated concrete has made certain progress. These studies have shown that through scientific activation treatment, iron tailings can be used as a partial substitute material for the production of green building materials with good mechanical properties and durability. However, despite this, its application in 3D printing concrete technology is still in its infancy. If iron tailings can be used instead of cement for 3D printable concrete, the cost of 3D printable concrete can also be reduced, but how to make it meet the requirements of buildability and printing accuracy of 3D printable concrete is still an urgent problem to be solved. Summary of the invention

[0005] In order to solve the problem of high cost of existing 3D printable concrete, the present invention provides an alkali-activated 3D printable concrete containing iron tailings and a preparation method thereof.

[0006] The technical solution of the present invention:

[0007] An alkali-activated 3D printable concrete containing iron tailings comprises the following components in parts by mass: 80 to 480 parts of iron tailings powder, 200 to 1200 parts of fly ash, 320 to 1920 parts of mineral powder, 200 to 1200 parts of steel slag, 1200 to 7200 parts of fine aggregate and 380 to 2280 parts of alkaline activator, wherein the fine aggregate consists of iron tailings sand and quartz sand, wherein the mass proportion of the iron tailings sand is 0 to 20%.

[0008] Furthermore, the average particle size of the iron tailings powder is 99.24 μm; the average particle size of the fly ash is 20.52 μm, the average particle size of the mineral powder is 12.18 μm, the average particle size of the steel slag is 135.15 μm, the average particle size of the iron tailings sand is 355.90 μm, and the average particle size of the quartz sand is 387.03 μm.

[0009] Furthermore, the iron tailings powder is first subjected to ball milling activation treatment before use, and the average particle size of the obtained activated iron tailings powder is 27.93 μm; the average particle size of the fly ash is 20.52 μm, the average particle size of the mineral powder is 12.18 μm, the average particle size of the steel slag is 135.15 μm, the average particle size of the iron tailings sand is 355.90 μm, and the average particle size of the quartz sand is 387.03 μm.

[0010] Furthermore, the ball milling media used in the ball milling activation treatment are stainless steel beads with diameters of 4 mm and 8 mm in equal mass ratio, the ball-to-material ratio is 2:1, the ball milling speed is 400 rpm, and the ball milling time is 30 to 120 min.

[0011] Furthermore, the alkaline activator is prepared from sodium silicate solution, NaOH and water, and the modulus after mixing is 1.5M.

[0012] A method for preparing alkali-activated 3D printable concrete containing iron tailings, comprising the following preparation steps:

[0013] Step 1: Prepare alkaline activator:

[0014] Step 2: Evenly mix the iron ore tailings powder, fly ash, mineral powder and steel slag, then add fine aggregate and continue to mix to obtain evenly distributed solid materials;

[0015] Step 3: adding an alkaline activator to the obtained solid material, stirring and mixing thoroughly to obtain a uniform concrete slurry;

[0016] Step 4: The obtained concrete slurry is cast and vibrated or 3D printed, and then cured to obtain iron tailings-based alkali-activated concrete.

[0017] Furthermore, the fluidity of the concrete slurry obtained in step 3 meets 190-250 mm.

[0018] Furthermore, the 3D printing in step 4 is to convey the concrete slurry obtained in step 3 to the print head of a desktop 3D printer. The 3D print head, under the control of a computer system, extrude layer by layer according to a set program, accumulates layer by layer, and completes 3D printing.

[0019] Furthermore, in step 4, the outlet diameter of the 3D printing nozzle is 10 mm; during the 3D printing, the 3D printing thickness is 10 mm, the horizontal printing speed is 200 to 300 m / h, the extrusion speed is 0.2 to 0.5 m3 / h, and the single continuous printing height is 10 to 240 mm.

[0020] Furthermore, the curing in step 4 is performed for 7 to 28 days at an ambient temperature of 20±2° C. and a relative humidity greater than 95%.

[0021] Beneficial effects of the present invention:

[0022] The present invention provides an alkali-activated 3D printable concrete containing iron tailings. The volcanic ash activity of the iron tailings powder itself is utilized and an alkali-activated concrete slurry with good fluidity is obtained by optimizing the component ratio. Through the dispersing effect of the iron tailings powder and the synergistic effect of other cementitious materials, not only the uniform dispersion of the cementitious materials in the slurry is enhanced, the dissolution of more silica-alumina glass phases is promoted and the participation in the hydration reaction is promoted, but also the constructability and printing accuracy in the 3D printing process are significantly improved.

[0023] The present invention further depolymerizes the iron tailings powder particles by mechanical grinding, and cracks are generated on the surface and inside of the particles, thereby refining the particles, increasing the specific surface area, exposing more active sites, and further activating its volcanic ash activity, so that it can generate more silica-alumina gels that are conducive to strength growth, and enhancing the mechanical properties of alkali-activated concrete. Mechanical grinding can also optimize the particle size distribution of the iron tailings powder, making the internal structure of the alkali-activated concrete more compact and the strength growth rate more obvious. The iron tailings-based alkali-activated concrete prepared by the present invention meets the standard of 32.5 grade of composite silicate cement in "General Portland Cement" (GB175-2007). Under standard curing conditions, the activity of alkali-activated concrete increased by 30.1% in the X direction at 7 days; 38.9% in the Y direction; 32.6% in the Z direction, and increased by 7.1% in the X direction at 28 days; 21.1% in the Y direction; 6.3% in the Z direction. This continuous strength growth is of great significance for improving the quality and reliability of 3D printed building structures.

[0024] Based on mechanically grinding activated iron tailings powder, the present invention realizes efficient utilization of iron tailings in building materials by replacing part of quartz sand with iron tailings sand as fine aggregate, and further optimizes the overall performance of 3D printed building structures. Compared with traditional cement-based concrete, the 3D printable alkali-activated concrete prepared by the present invention is a new type of construction method with lower energy consumption and carbon emissions during the preparation process, high technical feasibility, and good social and economic benefits, which is of great significance to the promotion and application of 3D printing technology in the field of construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a photo of a 3D printed specimen obtained by evaluating the constructability of 3D printing of alkali-activated concrete in Example 1;

[0026] Figure 2 This is a photo of a 3D printed specimen obtained by evaluating the constructability of 3D printing of alkali-activated concrete in Example 4;

[0027] Figure 3 This is a physical photo of the 3D printed specimen obtained by evaluating the constructability of alkali-activated concrete 3D printing in comparative example 1. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0029] Example 1

[0030] This embodiment provides an alkali-activated 3D printable concrete containing iron tailings and a preparation method thereof.

[0031] The specific preparation method of alkali-activated 3D printable concrete containing iron tailings in this embodiment includes the following steps:

[0032] Step 1: Prepare alkaline activator:

[0033] Dissolve 86.8g NaOH particles in 1203.1g water. After complete dissolution, add 929.0g industrial sodium silicate solution (Na2O / SiO2=2.3). Stir evenly to obtain a composite alkaline activator with a modulus of 1.5M. Let it stand at room temperature for 24 hours for use.

[0034] Step 2: Prepare solid materials:

[0035] Add 480g of iron tailings powder, 1200g of fly ash, 1920g of mineral powder and 1200g of steel slag into the mortar mixer in turn, and stir at a low speed of 62±5r / min for 1min; continue to add 7200g of quartz sand with an average particle size of 387.03μm into the mortar mixer as fine aggregate, and continue to stir at a low speed of 62±5r / min for 1min to obtain evenly distributed solid material.

[0036] The chemical composition and particle size of each raw material in this example are shown in Table 1.

[0037] Table 1

[0038]

[0039] Step 3: Preparation of alkali activated concrete paste:

[0040] The alkaline activator prepared in step 1 is slowly and evenly added into the mortar mixer, stirred at a low speed of 62±5r / min for 3 min, stopped stirring for 30 seconds, and then continued stirring at a stirring speed of 125±10r / min for 3 min, until the alkaline activator and the solid material are fully mixed to form a uniform alkali-activated concrete slurry. The fluidity of the alkali-activated concrete slurry is 234mm.

[0041] Step 4: Forming and maintenance:

[0042] The alkali-activated concrete paste obtained in step 3 is transported to the print head of the HC1008 desktop concrete 3D printer. The outlet diameter of the 3D print head is 10 mm. The 3D print head is controlled by the computer system and extrude layer by layer according to the set program. During 3D printing, the 3D printing thickness is 10 mm, the horizontal printing speed is 200 m / h, and the extrusion speed is 0.5 m 3 / h, 10 layers were printed cumulatively, and the single continuous printing height was 100mm. The 3D printing was completed and a 10-layer solid structure specimen was obtained.

[0043] The printed specimens were placed in a standard environment with a temperature of 20±2°C and a relative humidity greater than 95% for curing. After the specimens reached a curing age of 7d and 28d, mechanical properties tests were performed.

[0044] Example 2

[0045] This embodiment provides an alkali-activated 3D printable concrete containing iron tailings and a preparation method thereof.

[0046] The specific preparation method of alkali-activated 3D printable concrete containing iron tailings in this embodiment includes the following steps:

[0047] Step 1: Prepare alkaline activator:

[0048] Dissolve 86.8g NaOH particles in 1203.1g water. After complete dissolution, add 929.0g industrial sodium silicate solution (Na2O / SiO2=2.3). Stir evenly to obtain a composite alkaline activator with a modulus of 1.5M. Let it stand at room temperature for 24 hours for use.

[0049] Step 2: Prepare solid materials:

[0050] Add 480g of iron tailings powder, 1200g of fly ash, 1920g of mineral powder and 1200g of steel slag into the mortar mixer in turn, and stir at a low speed of 62±5r / min for 1min; continue to add 6480g of quartz sand with an average particle size of 387.03μm and 720g of iron tailings sand with an average particle size of 355.90μm into the mortar mixer as fine aggregate, and continue to stir at a low speed of 62±5r / min for 1min to obtain evenly distributed solid material.

[0051] The chemical composition and particle size of each raw material in this embodiment are shown in Table 1. The chemical composition of the iron tailings sand is the same as that of the iron tailings powder.

[0052] Step 3: Preparation of alkali activated concrete paste:

[0053] Slowly and evenly add the alkaline activator prepared in step 1 into the mortar mixer, stir at a low speed of 62±5r / min for 3 minutes, stop stirring for 30 seconds, and then continue stirring at a stirring speed of 125±10r / min for 3 minutes until the alkaline activator and the solid material are fully mixed to form a uniform alkali-activated concrete slurry. The fluidity of the alkali-activated concrete slurry is 215mm.

[0054] Step 4: Forming and maintenance:

[0055] The alkali-activated concrete paste obtained in step 3 is transported to the print head of the HC1008 desktop concrete 3D printer. The outlet diameter of the 3D print head is 10 mm. The 3D print head is controlled by the computer system and extrude layer by layer according to the set program. During 3D printing, the 3D printing thickness is 10 mm, the horizontal printing speed is 200 m / h, and the extrusion speed is 0.5 m 3 / h, 10 layers were printed cumulatively, and the single continuous printing height was 100mm. The 3D printing was completed and a 10-layer solid structure specimen was obtained.

[0056] The printed specimens were placed in a standard environment with a temperature of 20±2°C and a relative humidity greater than 95% for curing. After the specimens reached a curing age of 7d and 28d, mechanical properties tests were performed.

[0057] Example 3

[0058] This embodiment provides an alkali-activated 3D printable concrete containing iron tailings and a preparation method thereof.

[0059] The specific preparation method of alkali-activated 3D printable concrete containing iron tailings in this embodiment includes the following steps:

[0060] Step 1: Prepare alkaline activator:

[0061] Dissolve 86.8g NaOH particles in 1203.1g water. After complete dissolution, add 929.0g industrial sodium silicate solution (Na2O / SiO2=2.3). Stir evenly to obtain a composite alkaline activator with a modulus of 1.5M. Let it stand at room temperature for 24 hours for use.

[0062] Step 2: Prepare solid materials:

[0063] Add 480g of iron tailings powder, 1200g of fly ash, 1920g of mineral powder and 1200g of steel slag into the mortar mixer in turn, and stir at a low speed of 62±5r / min for 1min; continue to add 5760g of quartz sand with an average particle size of 387.03μm and 1440g of iron tailings sand with an average particle size of 355.90μm into the mortar mixer as fine aggregate, and continue to stir at a low speed of 125±10r / min for 1min to obtain evenly distributed solid material.

[0064] The chemical composition and particle size of each raw material in this embodiment are shown in Table 1. The chemical composition of the iron tailings sand is the same as that of the iron tailings powder.

[0065] Step 3: Preparation of alkali activated concrete paste:

[0066] Slowly and evenly add the alkaline activator prepared in step 1 into the mortar mixer, stir at a low speed of 62±5r / min for 3 minutes, stop stirring for 30 seconds, and then continue stirring at a stirring speed of 125±10r / min for 3 minutes until the alkaline activator and the solid material are fully mixed to form a uniform alkali-activated concrete slurry. The fluidity of the alkali-activated concrete slurry is 203mm.

[0067] Step 4: Forming and maintenance:

[0068] The alkali-activated concrete paste obtained in step 3 is transported to the print head of the HC1008 desktop concrete 3D printer. The outlet diameter of the 3D print head is 10 mm. The 3D print head is controlled by the computer system and extrude layer by layer according to the set program. During 3D printing, the 3D printing thickness is 10 mm, the horizontal printing speed is 200 m / h, and the extrusion speed is 0.5 m 3 / h, 10 layers were printed cumulatively, and the single continuous printing height was 100mm. The 3D printing was completed and a 10-layer solid structure specimen was obtained.

[0069] The printed specimens were placed in a standard environment with a temperature of 20±2°C and a relative humidity greater than 95% for curing. After the specimens reached a curing age of 7d and 28d, mechanical properties tests were performed.

[0070] Example 4

[0071] This embodiment provides an alkali-activated 3D printable concrete containing iron tailings and a preparation method thereof.

[0072] The specific preparation method of alkali-activated 3D printable concrete containing iron tailings in this embodiment includes the following steps:

[0073] Step 1: Prepare alkaline activator:

[0074] Dissolve 86.8g NaOH particles in 1203.1g water. After complete dissolution, add 929.0g industrial sodium silicate solution (Na2O / SiO2=2.3). Stir evenly to obtain a composite alkaline activator with a modulus of 1.5M. Let it stand at room temperature for 24 hours for use.

[0075] Step 2: Prepare solid materials:

[0076] According to the ball-to-material ratio of 2:1, 960g of stainless steel beads with particle sizes of 4mm and 8mm and 480g of iron tailings powder with an average particle size of 99.24μm were put into a planetary ball mill, and mechanically ground at a speed of 400rmp for 90min to obtain ball-milled iron tailings powder with an average particle size of 27.93μm;

[0077] Add 480g of ball-milled iron tailings powder, 1200g of fly ash, 1920g of mineral powder and 1200g of steel slag into the mortar mixer in turn, and stir at a low speed of 62±5r / min for 1min; continue to add 5760g of quartz sand with an average particle size of 387.03μm and 1440g of iron tailings sand with an average particle size of 355.90μm into the mortar mixer as fine aggregate, and continue to stir at a low speed of 125±10r / min for 1min to obtain evenly distributed solid material.

[0078] The chemical composition and particle size of each raw material in this embodiment are shown in Table 1. The chemical composition of the iron tailings sand is the same as that of the iron tailings powder.

[0079] Step 3: Preparation of alkali activated concrete paste:

[0080] Slowly and evenly add the alkaline activator prepared in step 1 into the mortar mixer, stir at a low speed of 62±5r / min for 3 minutes, stop stirring for 30 seconds, and then continue stirring at a stirring speed of 125±10r / min for 3 minutes until the alkaline activator and the solid material are fully mixed to form a uniform alkali-activated concrete slurry. The fluidity of the alkali-activated concrete slurry is 192mm.

[0081] Step 4: Forming and maintenance:

[0082] The alkali-activated concrete paste obtained in step 3 is transported to the print head of the HC1008 desktop concrete 3D printer. The outlet diameter of the 3D print head is 10 mm. The 3D print head is controlled by the computer system and extrude layer by layer according to the set program. During 3D printing, the 3D printing thickness is 10 mm, the horizontal printing speed is 200 m / h, and the extrusion speed is 0.5 m 3 / h, 10 layers were printed cumulatively, and the single continuous printing height was 100mm. The 3D printing was completed and a 10-layer solid structure specimen was obtained.

[0083] The printed specimens were placed in a standard environment with a temperature of 20±2°C and a relative humidity greater than 95% for curing. After the specimens reached a curing age of 7d and 28d, mechanical properties tests were performed.

[0084] Comparative Example 1

[0085] This comparative example provides a method for preparing alkali-activated concrete.

[0086] The specific preparation method of the alkali-activated concrete of this comparative example comprises the following steps:

[0087] Step 1: Prepare alkaline activator:

[0088] Dissolve 86.8g NaOH particles in 1203.1g water. After complete dissolution, add 929.0g industrial sodium silicate solution (Na2O / SiO2=2.3). Stir evenly to obtain a composite alkaline activator with a modulus of 1.5M. Let it stand at room temperature for 24 hours for use.

[0089] Step 2: Prepare solid materials:

[0090] Add 1680g of fly ash, 1920g of mineral powder and 1200g of steel slag into the mortar mixer in turn, and stir at a low speed of 62±5r / min for 1min; continue to add 7200g of quartz sand with an average particle size of 387.03μm into the mortar mixer as fine aggregate, and continue to stir at a low speed of 62±5r / min for 1min to obtain evenly distributed solid material.

[0091] The chemical composition and particle size of each raw material in this comparative example are shown in Table 1.

[0092] Step 3: Preparation of alkali activated concrete paste:

[0093] The alkaline activator prepared in step 1 was slowly and evenly added to the mortar mixer, stirred at a low speed of 62±5 r / min for 3 min, stopped stirring for 30 seconds, and then continued stirring at a stirring speed of 125±10 r / min for 3 min, until the alkaline activator and the solid material were fully mixed to form a uniform alkali-activated concrete slurry. The fluidity of the alkali-activated concrete slurry was 246 mm.

[0094] Step 4: Forming and maintenance:

[0095] The alkali-activated concrete paste obtained in step 3 is transported to the print head of the HC1008 desktop concrete 3D printer. The outlet diameter of the 3D print head is 10 mm. The 3D print head is controlled by the computer system and extrude layer by layer according to the set program. During 3D printing, the 3D printing thickness is 10 mm, the horizontal printing speed is 200 m / h, and the extrusion speed is 0.5 m 3 / h, 10 layers were printed cumulatively, and the single continuous printing height was 100mm. The 3D printing was completed and a 10-layer solid structure specimen was obtained.

[0096] The printed specimens were placed in a standard environment with a temperature of 20±2°C and a relative humidity greater than 95% for curing. After the specimens reached a curing age of 7d and 28d, mechanical properties tests were performed.

[0097] 1. The constructability of the alkali-activated concrete prepared in Examples 1 to 4 and Comparative Example 1 was evaluated. The specific evaluation method is as follows:

[0098] The alkali-activated concrete pastes obtained in step 3 of Example 1 to Example 4 and Comparative Example 1 were respectively conveyed to the print head of the HC1008 desktop concrete 3D printer. The outlet diameter of the 3D print head was 10 mm. The 3D print head was controlled by a computer system and extruded layer by layer according to a set program. During 3D printing, the thickness of each 3D print layer was 10 mm, the horizontal printing speed was 200 m / h, and the extrusion speed was 0.5 m / h. 3 / h, and 24 layers were printed layer by layer. The reagent height, interlayer connection and overall stability at each time were investigated.

[0099] Comparative Example 1 Evaluation of the constructability of 3D printed alkali-activated concrete The actual height of the 3D printed specimen was 215 mm, and the total printing height loss was relatively large. Figure 3 As shown, during the printing process, due to the high fluidity of the ratio, severe deformation such as buckling occurs, which eventually causes structural instability. This shows that the ratio of iron tailings powder in comparative example 1 is not suitable for the architectural application requirements of 3D printing technology.

[0100] Example 1 Evaluation of the constructability of 3D printed concrete by alkali-activated concrete The actual height of the 3D printed specimen was 220 mm. Compared with the proportion of comparative example 1 without iron tailings powder, the constructability of the specimen was improved as the fluidity decreased. Figure 1 As shown, during the layer-by-layer stacking process, there are still many poor connections and local extrusion phenomena between layers.

[0101] Example 2 Evaluation of constructability of alkali-activated concrete 3D printing The actual height of the obtained 3D printed specimen is 235 mm. During the extrusion process, the slurry is uniform and continuous, and the layers are tightly connected, ensuring the overall stability of the extruded structure.

[0102] Example 3 Evaluation of constructability of alkali-activated concrete 3D printing The actual height of the obtained 3D printed specimen is 234 mm. During the extrusion process, the slurry is uniform and continuous, and the layers are tightly connected, ensuring the overall stability of the extruded structure.

[0103] Example 4 Evaluation of constructability of 3D printing of alkali-activated concrete The actual height of the 3D printed specimen was 236 mm. Figure 2 As shown, the slurry is uniform and continuous during the extrusion process, and the interlayer connection is tight, ensuring the overall stability of the extruded structure. Compared with Example 1-Example 3, the iron tailings powder treated by mechanical grinding for 90 minutes has significantly enhanced hydration activity and greatly improved early compressive strength (7d). This not only improves the adverse effects of iron tailings on the compressive strength of concrete due to their low activity, but also further promotes the application potential of iron tailings in the field of 3D printing architecture.

[0104] 2. The mechanical property test results of the alkali-activated concrete prepared in Examples 1 to 4 and Comparative Example 1 are shown in Table 2.

[0105] Table 2

[0106]

[0107]

[0108] From the comparison of the data in Table 2, it can be seen that the alkali-activated concrete obtained in Examples 1 to 4 all meet the standard of grade 32.5 of composite silicate cement in "General Portland Cement" (GB175-2007).

[0109] Compared with the control group in Examples 1 to 3 that was not ball-milled, the alkali-activated concrete prepared by ball-milling the iron tailings powder generated more silica-alumina gel that was conducive to strength growth, had a denser internal structure, and a more obvious strength increase. When the mechanical grinding time was set to 90 minutes, the mechanical properties of the resulting alkali-activated concrete were most significantly improved. Under standard curing conditions, the activity of the alkali-activated concrete increased by 30.1% in the X direction, 38.9% in the Y direction, and 32.6% in the Z direction at 7 days, and by 7.1% in the X direction, 21.1% in the Y direction, and 6.3% in the Z direction at 28 days. This continuous strength increase is of great significance for improving the quality and reliability of 3D printed building structures.

[0110] On the basis of mechanically grinding iron tailings powder, iron tailings sand is used to replace part of quartz sand as fine aggregate, further realizing the efficient utilization of iron tailings in building materials. Figure 1 and Figure 2 It can also be seen from the comparison that the concrete slurry prepared by ball-milled iron ore tailings significantly improves the constructability and printing accuracy in the 3D printing process, and optimizes the overall performance of the 3D printed building structure, which is of great significance to the promotion and application of 3D printing technology in the field of construction.

Claims

1. An alkali-activated 3D printable concrete containing iron tailings, characterized in that: The invention comprises the following components in parts by weight: 80 to 480 parts of iron tailings powder, 200 to 1200 parts of fly ash, 320 to 1920 parts of mineral powder, 200 to 1200 parts of steel slag, 1200 to 7200 parts of fine aggregate and 380 to 2280 parts of alkaline activator, wherein the fine aggregate is composed of iron tailings sand and quartz sand, wherein the mass proportion of the iron tailings sand is 0 to 20%.

2. The alkali-activated 3D printable concrete containing iron tailings according to claim 1, characterized in that: The average particle size of the iron tailings powder is 99.24 μm; the average particle size of the fly ash is 20.52 μm, the average particle size of the mineral powder is 12.18 μm, the average particle size of the steel slag is 135.15 μm, the average particle size of the iron tailings sand is 355.90 μm, and the average particle size of the quartz sand is 387.03 μm.

3. The alkali-activated 3D printable concrete containing iron tailings according to claim 1, characterized in that: The iron tailings powder is first subjected to ball milling activation treatment before use, and the average particle size of the obtained activated iron tailings powder is 27.93 μm; the average particle size of the fly ash is 20.52 μm, the average particle size of the mineral powder is 12.18 μm, the average particle size of the steel slag is 135.15 μm, the average particle size of the iron tailings sand is 355.90 μm, and the average particle size of the quartz sand is 387.03 μm.

4. The alkali-activated 3D printable concrete containing iron tailings according to claim 3, characterized in that: The ball milling media used in the ball milling activation treatment are stainless steel beads with diameters of 4 mm and 8 mm in equal mass ratio, the ball-to-material ratio is 2:1, the ball milling speed is 400 rpm, and the ball milling time is 30 to 120 min.

5. An alkali-activated 3D printable concrete containing iron tailings according to any one of claims 1-4, characterized in that: The alkaline activator is prepared from sodium silicate solution, NaOH and water, and the modulus after mixing is 1.5M.

6. A method for preparing alkali-activated 3D printable concrete containing iron tailings as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: Step 1: Prepare alkaline activator: Step 2: Evenly mix the iron ore tailings powder, fly ash, mineral powder and steel slag, then add fine aggregate and continue to mix to obtain evenly distributed solid materials; Step 3: adding an alkaline activator to the obtained solid material, stirring and mixing thoroughly to obtain a uniform concrete slurry; Step 4: The obtained concrete slurry is cast and vibrated or 3D printed, and then cured to obtain iron tailings-based alkali-activated concrete.

7. The method for preparing alkali-activated 3D printable concrete containing iron tailings according to claim 6, characterized in that: The fluidity of the concrete slurry obtained in step 3 meets 190-250 mm.

8. The method for preparing an alkali-activated 3D printable concrete containing iron tailings according to claim 6 or 7, characterized in that: The 3D printing described in step 4 is to convey the concrete slurry obtained in step 3 to the printing nozzle of the desktop 3D printer. Under the control of the computer system, the 3D printing nozzle extrude layer by layer according to the set program, accumulates layer by layer, and completes the 3D printing molding.

9. The method for preparing alkali-activated 3D printable concrete containing iron tailings according to claim 8, characterized in that: Step 4: The outlet diameter of the 3D printing nozzle is 10 mm; during the 3D printing, the 3D printing thickness is 10 mm, the horizontal printing speed is 200-300 m / h, and the extrusion speed is 0.2-0.5 m 3 / h, single continuous printing height is 10~240mm.

10. The method for preparing alkali-activated 3D printable concrete containing iron tailings according to claim 9, characterized in that: The curing in step 4 is carried out for 7 to 28 days at an ambient temperature of 20±2° C. and a relative humidity greater than 95%.